Rehabilitation Protocol Variability Following Arthroscopic Bankart Repair and Remplissage for Management of Anterior Shoulder Instability: A Systematic Review - Juan B. Villarreal-Espinosa; Michael M. Reinold; Mohammad Khak; Mohammad J. Shariyate; Carol Mita; Jeffrey Kay; Arun J. Ramappa (International Journal of Sports Physical Therapy)
# Background